Altered neurobiological function of brainstem hypoglossal neurons in DiGeorge/22q11.2 Deletion Syndrome. (17th September 2017) - Wang, Xin; Bryan, Corey; LaMantia, Anthony-Samuel; Mendelowitz, David
Highlights: Hypoglossal neurons from LgDel animals have shorter duration and larger amplitude afterhyperpolarizations. Glutamate amplitudes in hypoglossal neurons are diminished in LgDel siblings. GABAergic events are less frequent in hypoglossal motor neurons in LgDel animals. Abstract: DiGeorge/22q11.2 Deletion Syndrome (22q11DS) is a common genetic microdeletion syndrome that underlies several neurodevelopmental disorders including autism, attention deficit/hyperactivity disorder, and schizophrenia. In addition to cognitive impairments, those with 22q11DS have disrupted feeding and swallowing from birth onward. This perinatal dysphagia significantly compromises nutritional status, impairs appropriate weight gain, and can lead to life threatening aspiration-based infections. Appropriately timed excitation and inhibition of brainstem hypoglossal motor neurons, which innervate tongue muscles, is essential for proper feeding and swallowing. In this study we have examined changes in hypoglossal motor neuron function in the LgDel mouse model of 22q11DS. Hypoglossal motor neurons from LgDel mouse pups have action potentials with afterhyperpolarizations, mediated by a large conductance charybdotoxin-sensitive Ca-activated K current, that are significantly shorter in duration and greater in magnitude than those in wild-type pups. In addition, the amplitude, but not frequency, of glutamatergic excitatory glutamatergic postsynaptic currents (EPSCs) is diminished, and GABAergic, but not glycinergic, neurotransmission to hypoglossal motor neurons was reduced in LgDel animals. These observations provide a foundation for understanding the neurological changes in hypoglossal motor neuron function and their contribution to swallowing abnormalities that occur in DiGeorge/22q11.2 Deletion Syndrome.